2022
DOI: 10.1111/jcpt.13659
|View full text |Cite
|
Sign up to set email alerts
|

No apparent pharmacokinetic interactions were found between henagliflozin: A novel sodium‐glucose co‐transporter 2 inhibitor and glimepiride in healthy Chinese male subjects

Abstract: What is known and objective Henagliflozin is a novel selective sodium‐glucose co‐transporter 2 (SGLT2) inhibitor with similar inhibitory effect to ertugliflozin. Glimepiride is widely used to treat type 2 diabetes mellitus (T2DM) with few cardiovascular side effects. In the present study, we aimed at evaluating the pharmacokinetic (PK) interactions between henagliflozin and glimepiride. Methods An open‐label, single‐centre, single‐arm, 3‐period, 3‐treatment, self‐control study was conducted in twelve healthy C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Other new similar compounds (Ipragliflozin, Luseogliflozin, Tofogliflozin, and Remogliflozin) are investigated in clinical studies. The most recent SGLT inhibitors are investigated using pharmacokinetic and pharmacodynamic analyses (Remoglicoflozin [36][37][38][39], Henaglicoflozin [40][41][42][43], and Licoglicoflozin [44][45][46][47]).…”
Section: Sglt-2 Inhibitors In Dm Therapymentioning
confidence: 99%
“…Other new similar compounds (Ipragliflozin, Luseogliflozin, Tofogliflozin, and Remogliflozin) are investigated in clinical studies. The most recent SGLT inhibitors are investigated using pharmacokinetic and pharmacodynamic analyses (Remoglicoflozin [36][37][38][39], Henaglicoflozin [40][41][42][43], and Licoglicoflozin [44][45][46][47]).…”
Section: Sglt-2 Inhibitors In Dm Therapymentioning
confidence: 99%
“…In terms of increasing the risk of urinary tract infection,henagli ozin has a better safety pro le than dapagli ozin, empagli ozin and canagli ozin.Hengagli ozin is mainly metabolized by UGT2B4/7, UGT1A9, UGT1A3, and UGT1A6, and is a substrate for BCRP and P-gp transporters. There were no drug interactions between hengagli ozin and metformin, glibenclamide, valsartan and warfarin that affected clinical application [34,[38][39][40] . Exposure to hengagli ozin was reduced when hengagli ozin was combined with rifampin.…”
Section: Introductionmentioning
confidence: 99%
“…7 Clinical data have shown that no dose adjustment is required when henagliflozin is combined with metformin, glimepiride, or valsartan. [8][9][10] A phase III trial showed that henagliflozin (5 and 10 mg) monotherapy effectively controlled blood glucose levels, reducing body weight and blood pressure. 11 The data for the marketed drug metformin showed that after oral administration of metformin hydrochloride tablets, blood concentration peaked after about 2.5 hours, with a terminal plasma clearance half-life of about 6.5 hours.…”
mentioning
confidence: 99%